An Exploratory Study of the Effect of Spanish Immersion Education on the Acquisition of Pronominal Subjects in Child Heritage Speakers - Goldin, Michele (Languages (Basel), 2020)
Studies have found that aspects of grammar that lie at the syntax–pragmatics interface, such as the use of pronominal subjects in null-subject languages, are likely to undergo cross-linguistic influence in bilingual speakers. This study contributes to our understanding of the role of Spanish immersion academic instruction on the comprehension of null subjects in English-dominant, Spanish-heritage children living in the United States. Two groups of bilingual children aged 4 to 7 (those attending a Spanish immersion school and those not) completed an acceptability judgment task in both English and Spanish. English monolingual children and monolingually raised Spanish children of the same ages also completed the task in their respective languages. The findings revealed that children in the Spanish immersion school performed on par with their monolingual peers in Spanish, but accepted significantly more ungrammatical null subjects in English than the other groups. These results suggest that immersion schooling plays a role in extending the English null subject stage in bilingual children due to competing input and cross-linguistic influence.